Mouse models of adrenal tumors responsive to gonadotropin-releasing hormone and gonadotropins - Pulawska K.; Doroszko M.; Chruściel M.; Ponikwicka-Tyszko D.; Wolczynski S.; Toppari J.; Huhtaniemi I.; Rahman N. (Elsevier Ltd, 2022)
In recent years, several mouse models have been established for characterization of the molecular pathways involved in adrenocortical tumorigenesis. Adrenal tumors develop in genetically susceptible mouse strains after prepubertal gonadectomy, in mice transgenic with oncogenes (simian virus 40 T antigen), several gene knockouts (such as inhibin or conditional Gata6F/F), and in mice overexpressing transcription factor GATA binding protein 4. The gonadal rest-type adrenal tumor phenotype is regulated by gonadotropins, mainly luteinizing hormone. Luteinizing hormone/chorionic hormone receptor and gonadotropin-releasing hormone receptor expression has been found in human adrenocortical carcinoma, as well as in several mouse adrenal tumor/adrenocarcinoma models. This mini-review will address recent advancements in this research topic with respect to the molecular basis of adrenocortical tumorigenesis, the clinical relevance of these tumor models, and the potential for future targeted treatment strategies. Furthermore, the ectopic expression of the luteinizing hormone/chorionic hormone receptor or gonadotropin-releasing hormone receptor may open up options for targeted therapy approaches.